2015
DOI: 10.3168/jds.2014-8821
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of early-lactation dairy cows as affected by dietary starch and monensin supplementation

Abstract: The objective of this study was to evaluate the effect of dietary starch content and monensin (MON) on metabolism of dairy cows during early lactation. Before parturition, primiparous (n=21) and multiparous (n=49) Holstein cows were fed a common controlled-energy close-up diet with a daily topdress of either 0 or 400mg/d monensin. From d 1 to 21 postpartum, cows were fed a high-starch (HS; 26.2% starch, 34.3% neutral detergent fiber, 22.7% acid detergent fiber, 15.5% crude protein) or low-starch (LS; 21.5% sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
48
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 44 publications
15
48
3
1
Order By: Relevance
“…The reduced ketogenesis was not coupled with any increase in the glucose concentrations in blood. Although not seen consistently (McCarthy et al 2015), an increased glucose level was reported in some previous studies with monensin (Duffield et al 2008b) and was also expected considering the numerical increase of C3 availability detected in the rumen fluid of our treated cows.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The reduced ketogenesis was not coupled with any increase in the glucose concentrations in blood. Although not seen consistently (McCarthy et al 2015), an increased glucose level was reported in some previous studies with monensin (Duffield et al 2008b) and was also expected considering the numerical increase of C3 availability detected in the rumen fluid of our treated cows.…”
Section: Discussionsupporting
confidence: 86%
“…Monensin is known to be effective in increasing the milk yield (MY) and can affect the milk components (Duffield et al 2008a(Duffield et al , 2008bMcCarthy et al 2015). Nevertheless, its effect on the casein content, titratable acidity, and clotting features of milk has been poorly investigated, and these are the focal points in cheesemaking systems.…”
Section: Introductionmentioning
confidence: 99%
“…All animals were clinically healthy before enrollment, and all diets fed to cows fell within normal composition ranges typically fed to transition dairy cows on commercial dairy farms in the United States. Longitudinal data for NEFA and BHBA concentrations from d 21 prepartum to 21 postpartum were recruited to address the present objective from 4 separate experiments [Smith et al (2008) Plasma concentrations (Smith et al, 2008;Yasui et al, 2014;McCarthy et al, 2015b) and serum concentrations (Mann et al, 2015) of NEFA were analyzed by enzymatic analysis using a commercial kit [HR Series NEFA HR (2), Wako Pure Chemical Industries, Osaka, Japan]. Data for NEFA were reported as microequivalents per liter and converted into millimoles per liter by multiplying by a factor of 0.001.…”
Section: Short Communicationmentioning
confidence: 99%
“…Feeding a highly saturated free fatty acid supplement in a low dietary forage neutral detergent fiber diet during the first 29 days postpartum might have primed the cows to limit fat mobilization at the expense of milk . McCarthy et al . reported that cows fed more propiogenic diets in early lactation (high starch or monensin) exhibited improved energy metabolism during early lactation.…”
Section: Energy Balance Assessmentmentioning
confidence: 99%
“…McCarthy et al15 reported that cows Likewise, reducing the number of diet changes before calving could facilitate ruminal adaptation to the lactation diet and improve energy balance postpartum 16. …”
mentioning
confidence: 99%